ASSESSMENT OF VARIOUS WATER-GAS-SHIFT PROCESS CONFIGURATIONS APPLIED TO PARTIAL OXIDATION ENERGY CONVERSION PROCESSES WITH CARBON CAPTURE - SANDU, Vlad-Cristian; CORMOS, Călin-Cristian; CORMOȘ, Ana-Maria (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The energy conversion systems based on partial oxidation processes (hydrocarbons catalytic reforming, solid fuel gasification) are very promising for integrating carbon capture technologies due to high CO2 partial pressure in syngas to be treated. In these systems, the water-gas-shift (WGS) reaction has a very important place in concentrating the syngas energy as hydrogen and to convert carbon species as CO2. This paper is evaluating various WGS process configurations to be applied in catalytic reforming and gasification designs ranging from the conventional designs (multiple catalytic shift reactors) to more innovative reactive gas-solid systems (chemical & calcium looping) for simultaneous syngas conversion and CO2 capture. As the evaluations show, the reactive gas-solid systems are more promising in reducing energy penalty for CO2 capture as well as to increase the overall energy efficiency and carbon capture rate. As illustrative examples, the coal gasification for hydrogen and power co-generation with carbon capture were assessed.